2013
DOI: 10.1038/nri3433
|View full text |Cite
|
Sign up to set email alerts
|

The ageing haematopoietic stem cell compartment

Abstract: Stem cell ageing underlies the ageing of tissues, especially those with a high cellular turnover. There is growing evidence that the ageing of the immune system is initiated at the very top of the haematopoietic hierarchy and that the ageing of haematopoietic stem cells (HSCs) directly contributes to changes in the immune system, referred to as immunosenescence. In this Review, we summarize the phenotypes of ageing HSCs and discuss how the cell-intrinsic and cell-extrinsic mechanisms of HSC ageing might promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
453
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 512 publications
(489 citation statements)
references
References 153 publications
28
453
0
8
Order By: Relevance
“…Taken with our previous observation that BM HSCs are increased in WT mice with aging, these data suggest that the Lxr αβ −/− mice may show a premature aging phenotype at 12 weeks. Furthermore, with aging, previous studies have also demonstrated preferential differentiation of HSCs toward the myeloid lineage over those in the lymphoid lineage 48. This is also consistent with the shift in myeloid cell numbers we observed in the Lxr αβ −/− versus WT mice basally at 12 weeks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken with our previous observation that BM HSCs are increased in WT mice with aging, these data suggest that the Lxr αβ −/− mice may show a premature aging phenotype at 12 weeks. Furthermore, with aging, previous studies have also demonstrated preferential differentiation of HSCs toward the myeloid lineage over those in the lymphoid lineage 48. This is also consistent with the shift in myeloid cell numbers we observed in the Lxr αβ −/− versus WT mice basally at 12 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…Stem cells are particularly sensitive to the effects of aging, where paradoxically, aging of HSCs increases their numbers in the BM 48. In accordance with this, we observed a 2‐fold increase in BM HSCs in the 20‐week‐old versus 12‐week‐old WT mice (Figures 1A and 3A).…”
Section: Discussionsupporting
confidence: 85%
“…Aging of HSCs was thought to be primarily regulated by cell intrinsic‐driven mechanisms (Morrison et al , 1996; Rossi et al , 2005; Chambers & Goodell, 2007; Geiger et al , 2013). In this study, we demonstrate a critical role for decreased OPN in osteoblasts in aged endosteal‐enriched stroma cells for inferring aging‐associated phenotypes on HSCs, while exposing old LT‐HSCs to OPN fragments activated by thrombin results in the attenuation of aging‐associated phenotypes and function of aged HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…While mechanisms through which the niche regulates young HSCs have started to be elucidated (Visnjic et al , 2004; Xie et al , 2009; Méndez‐Ferrer et al , 2010; Nombela‐Arrieta et al , 2013; Bruns et al , 2014; Acar et al , 2015; Gur‐Cohen et al , 2015), data on the extent of aging of the niche and the contribution to aging of HSCs are rare. Changes in the niche composition or function upon aging involve decreased bone formation, enhanced adipogenesis and changes in extracellular matrix (ECM) components (Calvi et al , 2003; Zhang et al , 2003; Naveiras et al , 2009; Geiger et al , 2013). Skewing of aged HSCs toward myeloid differentiation was recently linked to increased secretion of the pro‐inflammatory CC‐chemokine ligand 5 (CCL5; also known as RANTES) in aged stroma (Ergen et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic stem cells (HSCs) are adult stem cells from which, upon exposure to specific differentiation stimuli, all blood cells originate. In humans and rodent models, the number of HSCs isolated from bone marrow dramatically increases with age, whereas their capacity to proliferate in vitro in cloning formation assays (CFU‐F) and to repopulate the bone marrow of irradiated animals progressively decreases (Geiger et al ., 2013). Several groups have reported that murine HSCs accumulate DNA damage and senescence markers with age (Yahata et al ., 2011; Flach et al ., 2014).…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%